Structure–Activity Relationships and Therapeutic Potentials of 5-HT 7 Receptor Ligands: An Update - Modica, Maria N.; Lacivita, Enza; Intagliata, Sebastiano; Salerno, Loredana; Romeo, Giuseppe; Pittalà, Valeria; Leopoldo, Marcello (Journal of medicinal chemistry, 2018)
Serotonin 5-HT receptor (5-HT R) has been the subject of intense research efforts because of its presence in brain areas such as the hippocampus, hypothalamus, and cortex. Preclinical data link the 5-HT R to a variety of central nervous system processes including the regulation of circadian rhythms, mood, cognition, pain processing, and mechanisms of addiction. 5-HT R blockade has antidepressant effects and may ameliorate cognitive deficits associated with schizophrenia. 5-HT R has been recently shown to modulate neuronal morphology, excitability, and plasticity, thus contributing to shape brain networks during development and to remodel neuronal wiring in the mature brain. Therefore, the activation of 5-HT R has been proposed as a therapeutic approach for neurodevelopmental and neuropsychiatric disorders associated with abnormal neuronal connectivity. This Perspective celebrates the silver jubilee of the discovery of 5-HT R by providing a survey of recent studies on the medicinal chemistry of 5-HT R ligands and on the neuropharmacology of 5-HT R.